Dakwah Islam Populer dan Taar`uf di Kalangan Anak Muda Muslim Urban - Akhmad Ramidi (P3M STID Mustafa Ibrahim Al-Ishlahuddiny Kediri Lombok Barat, 2024)
One of the religious phenomena that has strengthened in the portrait of Islam in Indonesia is the emergence of the da'wah movement that voices the discourse of taaruf and piety among young urban Muslims. Inevitably, the emergence of this discourse as one of the counters to the narrative of promiscuity, one of which is the culture of dating. Although by definition taaruf and courtship have the meaning of knowing each other, courtship has been considered